2017
DOI: 10.2741/4572
|View full text |Cite
|
Sign up to set email alerts
|

NOK mediates glycolysis and nuclear PDC associated histone acetylation

Abstract: Functional genomics studies over the past decades have unveiled that the human genome transcribes a large amount of long noncoding RNAs (lncRNAs) which have been implicated in regulation of diverse cellular functions. Dysregulation of lncRNAs are often associated with human diseases including cancer. The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is among the most abundant and highly conserved lncRNAs. Emerging evidence has indicated that MALAT1 may have complex and extensive functions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In addition to these coding transcripts, the long noncoding transcript metastasis associated lung adenocarcinoma transcript 1 (MALAT1) was expressed in all cells from all patients. MALAT1 acts as a transcriptional regulator controlling expression of a number of genes involved in metastasis and prognosis in a variety of cancers [ 56 , 57 ], including lung cancer [ 58 ] and in PDAC [ 59 ]. In fact, in terms of expression levels, MALAT1 and CD74 were the 6 th & 7 th most highly expressed transcripts (for reference, mitochondrial 16S rRNA was the most highly expressed transcript, followed by 4 other mitochondrial genes).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these coding transcripts, the long noncoding transcript metastasis associated lung adenocarcinoma transcript 1 (MALAT1) was expressed in all cells from all patients. MALAT1 acts as a transcriptional regulator controlling expression of a number of genes involved in metastasis and prognosis in a variety of cancers [ 56 , 57 ], including lung cancer [ 58 ] and in PDAC [ 59 ]. In fact, in terms of expression levels, MALAT1 and CD74 were the 6 th & 7 th most highly expressed transcripts (for reference, mitochondrial 16S rRNA was the most highly expressed transcript, followed by 4 other mitochondrial genes).…”
Section: Resultsmentioning
confidence: 99%
“…MALAT1 expression has been shown to be either upregulated or downregulated in human cancers. On one hand, upregulation of MALAT1 was reported in lung cancer, hepatocellular carcinoma, breast cancer, and colorectal carcinoma, which has been extensively reviewed previously [23,24,25,26]. On the other hand, several studies showed that the expression of MALAT1 is downregulated in glioma [27], colorectal cancer [28], and breast cancer [29,30].…”
Section: Is Malat1 a Metastasis Promoter Or A Metastasis Suppressor?mentioning
confidence: 99%
“… 6 , 7 As one of the most abundant LncRNAs, MALAT1 is differentially expressed in various cancers, 8 , 9 with complex and extensive functions during the development and progression of the cancers. 10 Highly expressed in prostate cancer tissues and cell lines, it promotes the cells to proliferate and invade and inhibits their apoptosis in patients with prostate cancer. 11 In a study by Chen et al, the increasing expression of serum MALAT1 shortens the survival time of patients with EOC, so MALAT1 can be used as a biomarker for diagnosing metastasis.…”
Section: Introductionmentioning
confidence: 99%